HOPS/TMUB1 retains p53 in the cytoplasm and sustains p53‐dependent mitochondrial apoptosis. (23rd December 2019) - Castelli, Marilena; Piobbico, Danilo; Chiacchiaretta, Martina; Brunacci, Cinzia; Pieroni, Stefania; Bartoli, Daniela; Gargaro, Marco; Fallarino, Francesca; Puccetti, Paolo; Soddu, Silvia; Della‐Fazia, Maria Agnese; Servillo, Giuseppe
Abstract: Apoptotic signalling by p53 occurs at both transcriptional and non‐transcriptional levels, as p53 may act as a direct apoptogenic stimulus via activation of the intrinsic mitochondrial pathway. HOPS is a highly conserved, ubiquitously expressed shuttling protein with an ubiquitin‐like domain. We generated Hops −/− mice and observed that they are viable with no apparent phenotypic defects. However, when treated with chemotherapeutic agents, Hops −/− mice display a significant reduction in apoptosis, suggesting an impaired ability to respond to genotoxic stressors. We show that HOPS acts as a regulator of cytoplasmic p53 levels and function. By binding p53, HOPS inhibits p53 proteasomal degradation and favours p53 recruitment to mitochondria and apoptosis induction. By interfering with importin α, HOPS further increases p53 cytoplasmic levels. Thus, HOPS promotes the p53‐dependent mitochondrial apoptosis pathway by preserving cytoplasmic p53 from both degradation and nuclear uptake. Synopsis: Cytoplasmic p53 has important functions in apoptosis and autophagy. HOPS retains and stabilizes p53 in the cytoplasm and thereby promotes p53‐dependent mitochondrial apoptosis. Hops −/− mice are more resistant to DNA damage‐induced apoptosis. HOPS interacts with p53 and prevents its ubiquitylation and proteasomal degradation. HOPS promotes the mitochondrial accumulation of p53, which is a crucial step for apoptosis induction. HOPS retains p53 in the cytoplasm by competing with importin α‐mediated nuclear translocation. Abstract : Cytoplasmic p53 has important functions in apoptosis and autophagy. HOPS retains and stabilizes p53 in the cytoplasm and thereby promotes p53‐dependent mitochondrial apoptosis.